2010
DOI: 10.1186/1423-0127-17-s1-s32
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of taurine treatment and taurine deficiency on the outcome of renal ischemia reperfusion injury

Abstract: Taurine possesses membrane stabilization, osmoregulatory and antioxidant properties, aspects of relevance to ischemic injury. We tested the hypothesis that body taurine status is a determinant of renal ischemic injury. Accordingly, renal function and structure were examined in control (C), taurine-treated (TT) and taurine deficient (TD) rats that were subjected to bilateral renal ischemia (60 min) followed by reperfusion (IR); sham operated rats served as controls. Baseline urine osmolality was greater in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 45 publications
2
6
0
Order By: Relevance
“…However, it is possible that by understanding the metabolite pathways associated with renal injury, therapeutic options may be identified and a better understanding of the pathophysiology of the disease process can occur. Taurine is currently being evaluated as a preventive treatment for renal injury in various disease states 22–24 . Therefore, if we can confirm our findings in a larger trial, these preliminary data suggest taurine should be evaluated as a potential treatment to protect against renal injury in acute heart failure patients.…”
Section: Discussionsupporting
confidence: 65%
“…However, it is possible that by understanding the metabolite pathways associated with renal injury, therapeutic options may be identified and a better understanding of the pathophysiology of the disease process can occur. Taurine is currently being evaluated as a preventive treatment for renal injury in various disease states 22–24 . Therefore, if we can confirm our findings in a larger trial, these preliminary data suggest taurine should be evaluated as a potential treatment to protect against renal injury in acute heart failure patients.…”
Section: Discussionsupporting
confidence: 65%
“…Therefore, we analyzed cortical proximal tubules in PAN nephrotic model while focusing on ER stress, apoptosis, and subcellular organelles changes in the lysosomes and mitochondria. Intriguingly, our findings on the maintenance of cortical tubular dilatations in PAN pre-treated with TAU mice agreed with those of Mozaffari et al [ 72 ] who reported an apparent detrimental role of TAU in rat kidney after ischemia-reperfusion.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, taurine is known to be an important modulator and regulator of renal function, and it contributes to body-fluid and electrolyte homeostasis. This suggests a critical role for taurine in renal IR injury [ 27 , 28 ]. Like to taurine, the most important physiological roles for betaine are as an osmolyte and a methyl donor [ 29 ].…”
Section: Discussionmentioning
confidence: 99%